Comparison of surgically induced astigmatic changes after cataract surgery in post-Laser in situ keratomileusis corneas versus virgin eyes - Karslioglu, Melisa Zisan; Kesim, Cem; Tas, Ayse Yildiz; Hasanreisoglu, Murat; Muftuoglu, Orkun; Sahin, Afsun (Arquivos brasileiros de oftalmologia, 2023)
Postoperative refraction in modern mi-croincision cataract surgery gained extra importance in patients with the previous laser-assisted in situ keratomileusis (LASIK) surgery. The surgically induced astigmatic changes in those eyes may differ not only in magnitude but also in direction compared to virgin corneas. This study aimed to compare the surgically induced astigmatic changes after microscopic cataract surgery between post-LASIK corneas and virgin eyes. Cases that underwent microincision cataract surgery in eyes with and without previous LASIK surgery were reviewed. The demographics, the axial length at cataract surgery, the central corneal thickness, spheric and cylindric values, keratometry readings, and postoperative posterior corneal astigmatism were retrospectively evaluated. A modified Alpins method was used for astigmatic vector analysis, and baseline astigmatism, surgically induced astigmatism, difference vector, flattening effect, and torque were assessed. A total of 42 eyes from 24 subjects was evaluated. Group I consisted of 14 eyes with the previous LASIK, and Group II included 28 eyes without any refractive surgery. Preoperative mean central corneal thickness in Group I was significantly thinner (p=0.012). There was no significant difference in baseline astigmatism between the groups regarding magnitude and power vectors. After microincision cataract surgery, there were no significant differences in mean spheric and cylindric values and mean keratometry readings (all p>0.05). However, surgically induced astigmatism and difference vector were significantly higher on J45 vector component in post-LASIK eyes and microincision cataract surgery steepening effect on post-LASIK corneas was significantly higher than those in virgin eyes (p=0.001, p=0.002 and p=0.018, respectively). Cataract surgery has steepened the corneas in both groups with a significantly higher steepening effect in post-LASIK eyes. Certainly, corneal topography cataract surgery is particularly helpful to provide more precise surgically induced astigmatism interpretations.